Pelayanan Jasa Angkutan Ditinjau Dari KHES - Lubis, Nurhalimah (Jurnal El-Thawalib, 2022)
Madina Utama Travel is a company in the form of a CV that offers travel and tourism agents using cars with white paint. The formulation of the research problem is how the services provided by CV. Madina Utama Travel on passenger delivery? And how is the review of the Sharia Economic Law Compilation on the services provided by CV. Madina Utama Travel to passengers?. The purpose of this study was to obtain answers on how the services provided by CV. Madina Utama Travel and get answers on how the Sharia Economic Law Compilation review of the services provided by CV. Madina Utama Travel for passengers. According to KHES in Article 20 paragraph 1 what is meant by Akad is an agreement in an agreement between two or more parties to perform and or not to perform certain legal actions. This research is a field research that uses a descriptive qualitative approach in data collection. The data collection used in this research is the interview method (interview) observation method and documentation. Madina Utama Travel and passenger tickets. The time to conduct this research is about 2 months and the location of this research is on Jalan Jenderal Sudirman in front of the Sari Putra College, Sadabuan, Padangsidimpuan. The subject of this research is CV. Madina Utama Travel, driver and passenger. The terms of the contract have been fulfilled in accordance with the Sharia Economic Law Compilation. However, the driver violates the principle of trust and the principle of mutual benefit, resulting in breaking the promise made by the driver to the passenger, namely not delivering to the destination. This makes passengers feel disappointed because they are not delivered to their destination which is detrimental to time and costs. The driver did not carry out the agreed contract so that he did not carry out the services applied in CV. Madina Utama Travel.